TENDENCIAS Y VENTAJAS DE LA NUEVA RED SOCIAL THREADS EN LA COMUNIDAD ECUATORANA - ZURITA ARTEAGA, LESLEY GISSELLE (2024)
This research work addresses the trends and advantages of the new social network "Threads" in the Ecuadorian community, focusing on understanding and analyzing its impacts and uses on the population. Threads is presented as an emerging platform that has gained relevance in the digital scene, and seeks to explore how this social network influences social interactions, communication and participation in the community. The main objective of this study is to evaluate the trends and advantages of Threads in the Ecuadorian community, highlighting specific aspects such as the adoption of the platform, interaction patterns, and user perceptions regarding its benefits. It will be analyzed how Threads has modified the dynamics of social relationships, the dissemination of information and participation in virtual communities, identifying possible changes in digital content consumption habits. For data collection, two complementary methods will be used: individual interviews and online surveys. The interviews will provide a deeper, more qualitative perspective on the experience of Threads users, allowing you to explore specific details of their interactions and perceptions. Meanwhile, the online survey will be designed in a structured way to collect quantifiable data, covering a broader spectrum of users. The results obtained are expected to provide a clear view of the trends and advantages of Threads in the Ecuadorian community, supporting or questioning initial expectations. This study will contribute to understanding the impact of this new social network on the digital life of Ecuadorian users and will allow us to evaluate the relevance and effectiveness of Threads as a communication and connection tool in the digital age.